Effect of various fat sources on starter pig gut morphology and nutrient digestibility - D F Li; R C Thaler; D L Harmon; T L Weeden; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1989)
One digestion trial utilizing 24 weanling pigs was conducted to compare the effect of various fat sources on gut morphology and ileal nutrient digestibility. Diets had either no added oil (control) or were supplemented with 10% either soybean oil, coconut oil or a combination of soybean oil and coconut oil (1:1 ratio). Pigs were sacrificed on 29 d of age, and ileal digesta were collected. Villus height and crypt depth were measured at the midpoint of the small intestine. Results indicate that pigs fed the combination of soybean oil and coconut oil had longer villus height and slightly higher ileal digestibility of medium chain fatty acids compared to the pigs fed either soybean oil or coconut oil alone. The reduction of villus height caused by feeding soybean oil or coconut oil alone may decrease the absorptive area and could result in inadequate transport of nutrient at the villus surface. The net result is a decreased nutrient digestibility.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Pig; Small intestine; Digestibility; Fat